Identifying Vocabulary Learning Strategies Used by Undergraduate Students in Different Proficiency Levels - Nurmala Hendrawaty; Ayu Bandu Retnomurti (Loquen, 2021)
The aim of this study is to discover diverse vocabulary learning strategies among undergraduate students in three different competence levels (basic, intermediate, and advanced) who are enrolled in the Vocabulary course at Universitas Indraprasta PGRI in semester III. In this study, determination, social, memory, cognitive, and metacognitive methods were used to learn the language. Schmitt's Vocabulary Learning Strategies Questionnaire was used to collect data (VLSQ). Thirty undergraduate students were chosen on the basis of their competence levels. The results of descriptive statistics revealed that most undergraduate students used a medium strategy. The basic level had a mean score of 2.91, the intermediate level of 3.10, and the advanced level of 3.44. It was evident that the more vocabulary acquisition strategies a student used, the greater his or her competency level became. When it came to the most and least frequently utilized strategies by undergraduate students, metacognitive and determination were the most commonly employed techniques across three levels. However, the least frequent strategies of each level were different. Cognitive was slightly used by basic undergraduate students. Memory was the least employed by intermediate undergraduate students, and social was the fewest strategies implemented by advanced undergraduate students. This study revealed that the development of vocabulary learning strategies could increase EFL undergraduate students’ proficiency levels significantly.